2017
DOI: 10.1038/s41598-017-07216-6
|View full text |Cite
|
Sign up to set email alerts
|

Sex Specific Placental Accumulation and Behavioral Effects of Developmental Firemaster 550 Exposure in Wistar Rats

Abstract: Firemaster® 550 (FM 550) is a commercial flame retardant mixture of brominated and organophosphate compounds applied to polyurethane foam used in furniture and baby products. Due to widespread human exposure, and structural similarities with known endocrine disruptors, concerns have been raised regarding possible toxicity. We previously reported evidence of sex specific behavioral effects in rats resulting from developmental exposure. The present study expands upon this prior finding by testing for a greater r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 69 publications
(95 reference statements)
2
57
0
Order By: Relevance
“…FM 550 contains a mixture of organophosphates: (1) triphenyl phosphate (TPHP; previously abbreviated TPP); and (2) a mixture of isopropylated triphenylphosphate isomers (ITPs); as well as two brominated compounds (3) 2-Ethylhexyl-2,3,4,5-tetrabromobenzoate (TBB); and (4) bis(2-Ethylhexyl)-2,3,4,5-tetrabromophthalate (TBPH). Work by us and others have identified this mixture to be developmentally neurotoxic, endocrine disrupting, and obesogenic [5][6][7][8][9][10][11][12][13]. Human exposure is nearly ubiquitous with both gestational and lactational transfer as significant exposure routes in addition to direct exposure via household dust, which is inadvertently ingested or inhaled [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FM 550 contains a mixture of organophosphates: (1) triphenyl phosphate (TPHP; previously abbreviated TPP); and (2) a mixture of isopropylated triphenylphosphate isomers (ITPs); as well as two brominated compounds (3) 2-Ethylhexyl-2,3,4,5-tetrabromobenzoate (TBB); and (4) bis(2-Ethylhexyl)-2,3,4,5-tetrabromophthalate (TBPH). Work by us and others have identified this mixture to be developmentally neurotoxic, endocrine disrupting, and obesogenic [5][6][7][8][9][10][11][12][13]. Human exposure is nearly ubiquitous with both gestational and lactational transfer as significant exposure routes in addition to direct exposure via household dust, which is inadvertently ingested or inhaled [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In the heart, left ventricle thickness was also significantly increased in exposed males, suggesting impaired cardiovascular performance. The present study used bone tissue from animals derived from a subsequent, higher powered, study focused on neuroendocrine endpoints [8] to test for effects on bone density and microarchitecture with the hypothesis that males would be more vulnerable than females.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, although the placenta is meant to provide some protection for the fetus, a variety of environmental contaminants, including heavy metals, OPs, and flame retardants, have been shown to reach the fetus by passing through the placenta [157, 158]. Growing evidence that contaminants can accumulate in placental tissue [159163] emphasizes the possibility that the fetus may experience greater exposures than the mother. Therefore, during the gestational window, neurodevelopment can be impacted by direct toxicity to the developing brain, but also, indirectly, via direct toxicity to the placenta, leading to disrupted placental signaling factors critical for brain development including neurotransmitters and hormones.…”
Section: Indirect Toxicitymentioning
confidence: 99%
“…A study by Bailey and Levin (2015) revealed that the most sensitive indicator of FM-550's neurobehavioral toxicity in zebrafish is shoaling behavior, which was greatly affected by all doses of FM-550 following developmental exposure. Another study also showed that perinatal exposure to FM-550 at levels below no-observed-adverse-effect level (NOAEL) of 50 mg kg -1 day -1 has effects on the neurodevelopment of Wistar rats in a sex-specific manner (Baldwin et al, 2017). Behavioral outcomes of Baldwin's study showed heightened anxiety in male rats while hyperactivity was observed in female rats (Baldwin et al, 2017).…”
Section: Neurotoxicitymentioning
confidence: 99%
“…Another study also showed that perinatal exposure to FM-550 at levels below no-observed-adverse-effect level (NOAEL) of 50 mg kg -1 day -1 has effects on the neurodevelopment of Wistar rats in a sex-specific manner (Baldwin et al, 2017). Behavioral outcomes of Baldwin's study showed heightened anxiety in male rats while hyperactivity was observed in female rats (Baldwin et al, 2017). The contradictory result was found in Patisaul's report, which revealed heightened anxiety in female rats and not in males (Patisaul et al, 2013).…”
Section: Neurotoxicitymentioning
confidence: 99%